Metode Economic Order Quantity dalam Sistem Bandar Barang Bekas (SiBandar) - Cahya Vikasari; Riyadi Purwanto; Dwi Novia Prasetyanti (P3M Politeknik Negeri Cilacap, 2023)
Junk goods are no longer piles of worthless goods for businessmen who are keen to see the economic value by taking this opportunity by becoming a pelapak company to buy and sell junk goods purchased from collectors to be sold to buyers. The problems found with Pelapak include the manual recording of sales administration which has the potential to cause recording errors. Pelapak does not know for sure the stock of junk they own and those owned by collectors because the locations of the collectors are far apart. Orders of junk goods between pelapak and collectors are still via telephone so pelapak does not know which collectors are in the process of sending goods. Problems also occur on the part of collectors including unprofessional sales transactions. Based on these problems, a used goods stock management system is needed using the Economic Order Quantity (EOQ) method. The purpose of this study is to build a used goods stock management information system that can monitor the availability of used goods owned by collectors and pelapak. System development uses the prototype method and designs with concepts. The results of the research are that the system created can help find out the stock and the amount in each collector, recap sales reports, provide accurate information, facilitate business transactions and fulfill sales targets to buyers.